Management and Development of Community-Based Ecotourism Destinations in West Sumatra - Malse Yulivestra; Muhammad Ichsan Kabullah; Hendri Koeswara; Novalinda Novalinda (Universitas Andalas, 2023)
This research is based on the assumption that the government and the private sector are in control of the tourism industry which results in the position of the community being neglected and alienated. Therefore there is a need for efforts to empower local communities in managing and developing tourism potential in their area. The concept of Community based tourism is an alternative solution to restore the role and participation of the community in managing and developing this tourism sector. Based on this problem, the researcher tries to formulate research questions, namely; how is the management and development of community-based ecotourism destinations in West Sumatra? The objectives of this research include: 1) To describe and analyze how community-based ecotourism is managed and developed. 2) To describe the impact of community-based ecotourism management and development on the social, economic, and surrounding environment. The research method uses a qualitative approach with data collection techniques through field studies by collecting primary and secondary data. The data obtained will be reduced, presented and conclusions drawn which are the relationship between the existing theory and qualitative analysis which can provide an overview of the research problem. The results of the study explain that the management of ecotourism destinations in the research location is based on the community through tourism awareness groups formed by the community itself. The level of community participation is quite high both in planning, implementing, and evaluating management and development activities. As for the impact felt by the surrounding community, it is quite positive socially, economically and environmentally. In the future, there is a need to increase the capacity of tourism awareness groups as well as improve management and collaboration with other parties in improving suggestions and better ecotourism destinations.